Yom-ally has a 10.000 property damage liability, what means the insurance will pay that amound for propertie, and a 1000 deductible on her collision insurence so:
A) For the bike is a property of the other person so it will be paid with the insurance of $10000 dollars.
B)and it will pay the $600 dollars
C)her car will be paid with the insurance of collision of $1000 dollars
D)and will pay the $900 dollars
Answer:
35/37
Step-by-step explanation:
In this question, we are to calculate the ratio that represents the cosine of angle O
Firstly, please check attachment for diagram of the triangle.
Mathematically, the trigonometric term Cos means the ratio of the length of the adjacent to that of the hypotenuse
The hypotenuse is the longest length which is 37 which represents the length ON
The side adjacent to angle O is the side OP which is 35
Thus, the ratio representing the cosine of angle O is 35/37
So, here we have an exponential function.
Remember that an exponential function has the form:

Where a represents an initial amount, and r is the rate of this amount to change. (Increase, or decrease).
So, given that the population of City A in 2000 was 40 thousand people and the population increased by 13% each year, we can say that

So,

For city B:

But something different happens with city C. This is not an exponential function, this is a linear function.
So,

Hello there, my fellow human being!
So, the chicken costs $8 and the duck costs $5, here's why.
Let's say x is the cost of a chicken while y is the cost of a duck.
We can make two linear equations using the information above.
Last month, he sold 50 chickens and 30 ducks for $550: 50x + 30y= 550
This month, he sold 44 chicken and 36 ducks for $532: 44x + 36y = 532
50x/10 + 30y/10 = 440/10
44x/4 + 36y/4 = 532/4
5x + 3y = 44
11x + 9y = 133
So, now that we have our answer simplified, we have to use elimination to solve this system of equations. But, first we need to make sure that at least one of our variables is able to be canceled out.
Let's multiply this equation by -3.
(5x + 3y = 44) * -3.
-15x-9y=-165.
11x + 9y = 133
-15x - 9y = -165
______________
-4x/4 = -32/4
x = 8
11x + 9y = 133
11(8) + 9y = 133
88 + 9y = 133
-88 -88
________________
9y/9 = 45/9
y = 5.